Complete regularity and related concepts in L-uniform spaces - Harnett, Rait Sicklen (Rhodes University, Faculty of Science, Department of Mathematics, 1992)
L will denote a completely distributive lattice with an order reversing involution. The concept of an L-uniform space is introduced. An extension theorem concerning L-uniformly continuous functions is proved. A characterisation of L-uniformizability, involving L-complete regularity is given. With respect to L--completely regular spaces it is shown that the topological modification of an L-completely regular space is completely regular. Furthermore it is shown that the topologically generated L-topology of a completely regular space is L-completely regular.
Keywords: Uniform spaces; Mathematics -- Research